Computational modelling of objects represented in images fundamentals, methods and applications III - Di Giamberardino, Paolo (CRC Press, 2012)
Computational Modelling of Objects Represented in Images: Fundamentals, Methods and Applications III addresses different techniques, such as optimization methods, geometry, finite element method, principal component analysis, stochastic methods, neural networks and fuzzy logic. The book is useful to researchers and students with multidisciplinary interests related to Computational Vision, Computational Mechanics, Medicine, Engineering and Architecture.